From genotype to phenotype: Are there imaging characteristics associated with lung adenocarcinomas harboring RET and ROS1 rearrangements?. Issue 2 (November 2015) - Plodkowski, Andrew J.; Drilon, Alexander; Halpenny, Darragh F.; O'Driscoll, Dearbhail; Blair, Donald; Litvak, Anya M.; Zheng, Junting; Moskowitz, Chaya S.; Ginsberg, Michelle S.
Highlights: Radiogenomics can try to characterize the appearance of different lung cancers. Lung adenocarcinomas with RET and ROS1 fusions share many radiographic features. ROS1 tumors present as more peripheral lesions. Genetic testing in lung adenocarcinoma can offer additional targeted treatment. Abstract: Introduction: Recurrent gene rearrangements are important drivers of oncogenesis in non-small cell lung cancers. RET and ROS1 rearrangements are each found in 1–2% of lung adenocarcinomas and represent distinct molecular subsets. This study assessed the computed tomography (CT) imaging features of patients with RET - and ROS1 -rearranged lung cancers. Methods: Eligible patients included pathologically-confirmed lung adenocarcinomas of any stage with a RET or ROS1 rearrangement via fluorescence in-situ hybridization or next-generation sequencing, and available pre-treatment baseline imaging for review. A cohort of EGFR -mutant lung cancers was identified as a control group. CT features assessed included location, consistency, contour, presence of cavitation, and calcification of the primary tumor. Presence of an effusion, lung metastases, adenopathy and extrathoracic disease were recorded. The Wilcoxon rank-sum/Kruskal–Wallis and Fisher's exact tests were used to compare features between groups. Results: 73 patients with lung adenocarcinomas were identified: 17 (23%) with ROS1 fusions, 25 (34%) with RET fusions and 31 (43%) with EGFR mutations. ROS1 -rearranged lung cancers were more likely to present as peripheral tumors in comparison to EGFR -mutant lung cancers (32% vs. 65%, p  = 0.04). RET -rearranged lung cancers did not significantly differ from EGFR -mutant lung cancers radiographically. The consistency of the primary lesion for RET and ROS fusions and EGFR mutations were most frequently solid and spiculated. Conclusions: Lung adenocarcinomas with RET and ROS1 fusions share many radiographic features and those with ROS1 fusions are more likely to present as peripheral lesions in comparison to EGFR -mutant lung cancers.